Posted by **Whitney** on Monday, January 30, 2012 at 12:43pm.

If you square the equation v=v0 + at, you'll have an expression for v2. Equate the two expressions for v2, and show that the resulting equation reduces to the equation x= x0+v0t + 1/2at2.

Friday

March 24, 2017
Posted by **Whitney** on Monday, January 30, 2012 at 12:43pm.

If you square the equation v=v0 + at, you'll have an expression for v2. Equate the two expressions for v2, and show that the resulting equation reduces to the equation x= x0+v0t + 1/2at2.

Search